Securicauda hermani and Carinacauda stormi, two new genera and species of slug from the Pacific Northwest of the United States (Gastropoda: Stylommatophora: Arionidae), with notes on Gliabates oregonius Webb 1959 - Leonard, William P.; Chichester, Lyle; Richart, Casey H.; Young, Tiffany A. (Zootaxa, 2011)
Two new genera and species of arionid slug, Securicauda hermani n. gen. et n. sp. and Carinacauda stormi n. gen. et n. sp., are described from the United States in northern Idaho and western Oregon, respectively. This taxonomic decision is based on anatomical comparisons to the ten genera of Arionidae native to northwestern North America. Securicauda lacks an atrium and atrial accessory structures and the epiphallus is almost entirely buried in the penis; Carinacauda has an atrium, a pair of atrial accessory structures, and a long epiphallus that is not embedded in the penis.